Synthesis and Quality Control of Calcium Chelidonate Substance with Osteogenic Activity - E. Yu. Avdeeva; N. M. Igidov; V. L. Gein; S. V. Krivoshchekov; I. A. Khlusov; M. V. Belousov; N. V. Dozmorova; V. G. Luzhanin (Разработка и регистрация лекарственных средств)
Introduction. Osteogenic agents are used for pathologies associated with impaired bone formation, complications of bone fractures, the use of implants and endoprostheses, and tumor lesions of bone tissue. High osteogenic activity in vivo on the model of experimental osteomyelitis, in vitro and in situ on mesenchymal stem cells was revealed for calcium chelidonate, which is a promising substance for the production of osteogenic drugs.Aim. Development of a method for obtaining the calcium chelidonate substance by chemical synthesis and methods of its standardization.Materials and methods. The synthesis of chelidonic acid was carried out on the basis of diethyloxalate; calcium chelidonate – using synthesized chelidonic acid and anhydrous calcium chloride. The structure of the substances was confirmed by optical spectral methods, mass spectrometry, elemental and X-ray structural analysis. The quantitative content was assessed using a liquid chromatograph. Statistical processing of the results of quantitative measurements was carried out in the STATISTICA 8,0 program.Results and discussion. As a result of the synthesis, chelidonic acid (4-oxo-4H-piran-2,6-dicarboxylic acid) was obtained, which is colorless or cream-tinged crystals. The structure of the resulting compound is confirmed by spectral characteristics and elemental analysis data. A method for obtaining the calcium chelidonate substance has been worked out, while the yield of the target product was 100 ± 5 %. By X-ray structural analysis, it was found that the synthesized compound is calcium chelidonate trihydrate [Ca(ChA)(H2O)3]n with M.M. (C7H8O9Ca) 276,15. Methods for establishing authenticity, purity and quantification of the substance have been developed. The amount of impurities in the resulting substance did not exceed 0.1 %, and the content of the main component ranged from 99,2 ± 0,20 to 100,4 ± 0,35 %.Conclusion. Due to the limited resource reserves and the complexity of the process of extracting chelidonic acid from plant raw materials, a method for the chemical synthesis of calcium chelidonate substance with osteogenic activity is proposed. The obtained results provide prospects for further research in the direction of the development and introduction of synthetic calcium chelidonate as a new osteogenic drug, provided that the specific biological activity is comparable to the natural analogue.